(untitled) (Historia, 2021)
The composer of this atlas is Bernard Lugan, expert on African history, for 10 years professor and archaeologist at Kigale, Ruanda, at present professor in the University of Lyons. He has published several articles and books, some journalistic, inter alia on South Africa, which he visited at least five times.